On the origin of the non-Arrhenius Na-ion conductivity in Na3OBr - Darminto, B; Rees, GJ; Cattermull, J; Hashi, K; Diaz-Lopez, M; Kuwata, N; Turrell, SJ; Milan, E; Chart, Y; Di Mino, C; Lee, HJ; Goodwin, AL; et al. (Wiley, 2023)
The sodium-rich antiperovskites (NaRAPs) with composition Na3OB (B=Br, Cl, I, BH4, etc.) are a family of materials that has recently attracted great interest for application as solid electrolytes in sodium metal batteries. Non-Arrhenius ionic conductivities have been reported for these materials, the origin of which is poorly understood. In this work, we combined temperature-resolved bulk and local characterisation methods to gain an insight into the origin of this unusual behaviour using Na3OBr as a model system. We first excluded crystallographic disorder on the anion sites as the cause of the change in activation energy; then identified the presence of a poorly crystalline impurities, not detectable by XRD, and elucidated their effect on ionic conductivity. These findings improve understanding of the processing-structure-properties relationships pertaining to NaRAPs and highlight the need to determine these relationships in other materials systems, which will accelerate the development of high-performance solid electrolytes.